Analysis of Smart Indonesia Card Policy in Reducing School Dropout Rates in Indonesia: A Literature Study Perspective - Ria Maharani; Devi Novitasari; Erinaldi Erinaldi (Global Education Journal, 2025)
The Smart Indonesia Card (KIP) program is a public policy designed to expand access to education for children from underprivileged families and realize equal distribution of learning opportunities throughout Indonesia. This study aims to analyze the effectiveness of the implementation of the KIP policy in reducing the dropout rate and review the supporting and inhibiting factors in its implementation. The method used is a literature study with a descriptive qualitative approach, referring to Mustari's public policy theory in Suaib et al. (2022) which highlights four main elements: Input, goals, instruments, and impact. The data was obtained through a review of scientific journals, official government reports, and national news related to the implementation of KIP. The results of the analysis show that the KIP policy plays an important role in reducing the dropout rate and increasing educational participation, especially in urban areas. However, the effectiveness of the program still faces obstacles in the form of inaccurate recipient data, delays in disbursement of funds, and limited educational infrastructure in the 3T area. The positive impact can be seen from the increasing public awareness of the importance of education and the opening of opportunities for equal access to learning. In conclusion, KIP is a socially effective policy but is not fully optimal in terms of administration and technology. Strengthening the integrated data system, increasing digital literacy, and adjusting the nominal amount of assistance are strategic steps to increase sustainability and equitable distribution of program benefits.